Impact of Fiscal Policies on Western Balkan SMEs’ Growth: Evidence from Kosovo - Gezim Jusufi; Fillorete Gashi-Sadiku (Central European Public Administration Review)
This paper analyses the impact of fiscal policies on increasing the capacity of SMEs from the manufacturing sector in the Western Balkans, with particular emphasis on those in Kosovo. To achieve empirical results, the data obtained from the opinions of the 100 analysed SMEs were processed through logistic regression. The SPSS statistical software was also used for these statistics. Based on literature review and empirical results, it has been concluded that fiscal policies have an impact on Kosovo SMEs growth. Also in Kosovo and in other Western Balkan countries, fiscal policies and packages have been adopted to support SMEs and have had a significant effect on their activities. Despite the fact that under normal circumstances fiscal support for SMEs has been provided by the governments of these countries, in the near future there should be greater fiscal support to SMEs by means of fiscal incentives due to the devastating effects of the COVID 19 pandemic on each country’s economy.